2009
DOI: 10.1080/14786410802242778
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arthritic activity of various extracts ofSida rhombifoliaaerial parts

Abstract: Aerial parts of the plant Sida rhombifolia Linn. (Malvaceae) were extracted successively to produce various extracts. These extracts were screened for various parameters of anti-arthritic activity, such as adjuvant-induced arthritis, motor performance, mean distance travelled, and histopathological study. Results showed that the polar constituents (ethanol and aqueous extracts) of the plant S. rhombifolia were useful in the treatment of arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…In another report, it has been discussed that methanolic extract of its aerial part showed anti-inflammatory activity in animal model study [22]. Ethanol and aqueous extracts of aerial parts of the plant were also reported to be useful in the treatment of arthritis [23]. A recent report from experimental result of Ranjan et al [24] also showed significant anti diarrheal activity of methanolic extract of Sida rhombifolia.…”
Section: Introductionmentioning
confidence: 85%
“…In another report, it has been discussed that methanolic extract of its aerial part showed anti-inflammatory activity in animal model study [22]. Ethanol and aqueous extracts of aerial parts of the plant were also reported to be useful in the treatment of arthritis [23]. A recent report from experimental result of Ranjan et al [24] also showed significant anti diarrheal activity of methanolic extract of Sida rhombifolia.…”
Section: Introductionmentioning
confidence: 85%
“…SR is a small erect under shrub having rough branches with stellate hairs commonly found in dry countries such as India and Ceylon [ 218 ]. Traditionally, the plant is used as nutritive, tonic and for the treatment of gonorrhea, piles, rheumatism, as diuretic, and aphrodisiac [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The aqueous and ethanol extract of aerial parts of the SR at doses 30 and 100 mg/kg reduced the paw edema induced by CFA method. Thus, it is concluded that the plant possess a potent anti-arthritic activity [ 218 ].…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization (WHO) presently inspires, recommends and encourages traditional remedies in health care plans as they're simply obtainable at low value, relatively harmless and traditionally common [9]. The plant growths leads to the production various chemical compounds are called phytochemicals and refer as "secondary metabolites" that consist, flavonoids, alkaloids, coumarins, tannins, phenols, phlobatannins, anthraquinones, terpenoids, cardiac glycosides, steroid and phytosteroid [10]. It is known that the phytochemical compounds identified have medicinal significance.…”
Section: Quantitative and Qualitative Identification Ofmentioning
confidence: 99%